Study on the effect of using multi-round citric acid bottom vacuum leaching to remediate Cu, Zn-contaminated soil - Xueke Zang; Yanran Zhang; Haofan Yue (Frontiers in Environmental Science, 2025)
Bottom vacuum-enhanced leaching technology is an effective method for remediation of low-permeability contaminated soil. In order to clarify the influence of drenching rounds on the remediation effect of copper and zinc contaminated soil and soil properties, the change rule of heavy metal removal efficiency and soil properties under different rounds was analyzed through three rounds of citric acid bottom vacuum drenching model test, combined with one-dimensional compression test and microscopic test. The results showed that the leaching rounds had a significant effect. With the increase of the number of rounds, the removal rate of copper and zinc, porosity, permeability coefficient and consolidation coefficient were increased, and the particle size of soil particles was reduced. Microscopically, the structure of the soil samples was looser, and the pore size was enlarged by citric acid corrosion, which promoted the improvement of infiltration and consolidation properties. This study not only elucidated the mechanism of optimizing the pore structure to enhance the remediation effect by washing rounds, but also provided theoretical and technical references for the promotion of the bottom vacuum washing technology and the assessment of geotechnical properties of the remediated soil.